Competition parity and the Australian football league: 2000 – 2010 / Chris Davies - Davies, Chris (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2013)
Like many professional leagues around the world, the Australian Football League (AFL) has implemented labour market controls in order to try and create a more even competition. Since the 1980s both a salary cap and a draft system have been implemented in the quest for this objective. Under the Nordenfelt restraint of trade test the AFL is required to show that these controls have created a more even competition, and while the actual measuring of the evenness of a competition is problematic, it is suggested that the AFL can point to a number of factors to help support its claim that it has created a more even competition. These are the fact that during the period from 2000-09, all 16 AFL teams made the finals at least once, nearly 70 per cent of the teams reached their finals quota, while seven different teams won the premiership. It should be acknowledged that these labour market controls also place restrictions on the clubs in regard to what players they can recruit, and a study of the premiership teams from 2000-10 indicate that a number of different strategies have been successfully adopted by the clubs to create a premiership winning side.